Evaluation of universal design requirements application in public mosque in Bandung - Rangga, Firmansyah; Utaberta, Nangkula; Shaari, Nazlina; Ismail, Sumarni; W., Ratri (Malaysian Public Health Physicians' Association, 2020)
A Number of studies have found the cases of facilities in public buildings which are inaccessible by users & visitors with different abilities. Thus, constructing user friendly and barrier-free architecture-interior design is necessary in the built environment. This research will evaluate the requirements for ease of access in public mosques with study cases Pusdai Mosque & Grand Mosque of Bandung in accordance with the Regulation of the Ministry of Public Works and Public Housing of the Republic of Indonesia No.14 2017. The regulation which stipulates the provision of facilities in buildings and environments that suit the needs of all age groups, conditions of physical; mental; and intellectual; or sensory limitations based on the buildings’ function to provide user and visitor convenience in doing activities in the buildings. Both mosques, the Pusdai Mosque and Grand Mosque have not entirely fulfilled the standards of universal design in the interior in term of ease of access, safety and autonomy of space use, safety and security for all. From 7 universal design standard requirements, both mosques of study case only fulfill less than 50% of the requirements.